Предмет: Алгебра,
автор: Tati111
(x^2-5x)^2-2(x^2-5x)-24=0
Помогите пожалуйста
Ответы
Автор ответа:
0
(x^2-5x)^2-2(x^2-5x)-24=0 (x^2-5x)=y
y^2-2y-24=0
D=(2)^2-4*1*(-24)=4+96=100
x1/2=(2+10)/2
x1=(2-10)/2=-8/2=-4
x2=(2+10)/2=12/2=6
(x^2-5x)=((-4)^2-5*(-4))=16-(-24)=40
(x^2-5x)=(6)^2-5*6=36-30=6
y^2-2y-24=0
D=(2)^2-4*1*(-24)=4+96=100
x1/2=(2+10)/2
x1=(2-10)/2=-8/2=-4
x2=(2+10)/2=12/2=6
(x^2-5x)=((-4)^2-5*(-4))=16-(-24)=40
(x^2-5x)=(6)^2-5*6=36-30=6
Похожие вопросы
Предмет: Алгебра,
автор: farida19781213
Предмет: Математика,
автор: bbfaiter2
Предмет: Биология,
автор: winks2007
Предмет: Физика,
автор: Ekaterina2490
Предмет: Химия,
автор: xxxzooro